2008
DOI: 10.1039/b802660m
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteriochromes: a new superfamily of tetrapyrrole-binding photoreceptors in cyanobacteria

Abstract: A new group of photoreceptors has been experimentally revealed in cyanobacteria. They are phototaxis regulator SyPixJ1, TePixJ and AnPixJ, chromatic acclimation regulator SyCcaS, circadian input kinase homolog SyCikA and many other candidates, which have been found only in cyanobacteria to date. These new photoreceptors are now proposed to be "cyanobacteriochromes". They are characterized by the presence of a chromophore-binding GAF domain that is homologous to the tetrapyrrole-binding GAF domain of the phytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
334
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(340 citation statements)
references
References 65 publications
3
334
0
3
Order By: Relevance
“…Similarly, it has been suggested that two-Cys CBCRs can sense the cellular redox potential via oxidation of the second Cys, which arrests the photocycle (21). There also are many examples of tandem CBCR sensors containing multiple GAF domains that perceive light of various colors (1,2,14,19,23,24). CBCRs thus are exceptionally sophisticated photosensors, able to integrate light with various physiological cues and to provide complete coverage of the entire visible spectrum with a single chromophore precursor and a small, soluble protein sensor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been suggested that two-Cys CBCRs can sense the cellular redox potential via oxidation of the second Cys, which arrests the photocycle (21). There also are many examples of tandem CBCR sensors containing multiple GAF domains that perceive light of various colors (1,2,14,19,23,24). CBCRs thus are exceptionally sophisticated photosensors, able to integrate light with various physiological cues and to provide complete coverage of the entire visible spectrum with a single chromophore precursor and a small, soluble protein sensor.…”
Section: Discussionmentioning
confidence: 99%
“…S1B). * Cyanobacteriochromes (CBCRs) are widespread cyanobacterial photosensors with phytochrome-related GAF domains (1,2,13,14). Although CBCRs also convert between two photostates via bilin photoisomerization at C15, they exhibit much more spectral diversity, with peak absorptions ranging from 330 to 680 nm and hence spanning the entire visible spectrum and near UV (13,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…They are related to the red/far red responsive canonical phytochromes (Phys), 2 but absorb light at different wavelengths; the absorptions of the different CBCRs nearly cover the entire visible spectrum. 1,3,4 In contrast to canonical Phys, the sensory modules of CBCRs consist of several GAF domains (GAF, acronym of cGMP phosphodiesterase, adenylyl cyclase and FhlA protein domain), of which one or more bind covalently open-chain tetrapyrroles as photoactive chromophores.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] There are several advantages of Phys 10 and CBCRs, 1 or domains thereof, that make them potentially interesting tools in biological analytics: they can be obtained by heterologous co-expression of protein-and chromophorecoding genes; and chromophore attachment is autocatalytic and does not require co-expression of lyases. 11 Their use as fluorescent biomarkers is impaired, however, by the relatively low fluorescence quantum yield.…”
Section: Introductionmentioning
confidence: 99%
“…We like to think that as humans we have a highly developed sense of colour vision, but even these cyanobacteria are able to detect light of different wavelengths. 30,31 Why should these primitive organisms need such a complex system of chromatic detection? Cyanobacteria live in water columns, which at the surface are illuminated by light of a wide variety of wavelengths but where at depth blue light predominates.…”
Section: Evolution Of Visionmentioning
confidence: 99%